A Type IIa crustin from the pink shrimp Farfantepenaeus paulensis (crusFpau) is constitutively synthesized and stored by specific granule-containing hemocyte subpopulations. Issue 97 (February 2020) - Bandeira, Paula Terra; Vernal, Javier; Matos, Gabriel Machado; Farias, Natanael Dantas; Terenzi, Hernán; Pinto, Aguinaldo Roberto; Barracco, Margherita Anna; Rosa, Rafael Diego
Abstract: Crustins are cysteine-rich antimicrobial peptides (AMPs) widely distributed across crustaceans. From the four described crustin Types (I to IV), crustins from the subtype IIa are the most abundant and diverse members found in penaeid shrimp. Despite the critical role of Type IIa crustins in shrimp antimicrobial defenses, there is still limited information about their synthesis and antimicrobial properties. Here, we report the subcellular localization and the antibacterial spectrum of crus Fpau, a Type IIa crustin from the pink shrimp Farfantepenaeus paulensis . The recombinantly expressed crus Fpau showed antimicrobial activity against both Gram-positive and Gram-negative bacteria at low concentrations. Results from immunofluorescence using anti-rcrus Fpau antiserum revealed that crus Fpau is synthetized and stored by both granular and semigranular hemocytes, but not by hyaline cells. Interestingly, not all granular and semigranular hemocytes stained for crus Fpau, revealing that this crustin is produced by specific granule-containing hemocyte subpopulations. Finally, we showed that the granule-stored peptides are not constitutively secreted into the plasma of healthy animals. Highlights: The Type IIa crustin crus Fpau shows a broad range of antibacterial activity. crus Fpau is produced by specific granule-containing hemocyte subpopulations. crus Fpau is not constitutively secreted to shrimp plasma.